2017
DOI: 10.1002/anie.201610274
|View full text |Cite
|
Sign up to set email alerts
|

Enolonium Species—Umpoled Enolates

Abstract: Enolonium species/iodo(III)enolates of carbonyl compounds have been suggested to be intermediates in a wide variety of hypervalent iodine induced chemical transformations of ketones, including α-C-O, α-C-N, α-C-C, and α-carbon-halide bond formation, but they have never been characterized. We report that these elusive umpoled enolates may be made as discrete species that are stable for several minutes at -78 °C, and report the first spectroscopic identification of such species. It is shown that enolonium specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 42 publications
2
60
0
2
Order By: Relevance
“…According to the calculated interaction energies, the intermediate interacting through the O atom (mode A) is more favorable than that interacting through the C atom (mode B). Our present understanding of the mechanism involves attack of silyl enol ether 1 at the iodine atom of XB‐activated ylide 2 to form an enolonium species, with the subsequent rearrangement furnishing 1,4‐dicarbonyl compounds 3 . However, further mechanistic studies are in progress to distinguish between this and other possible mechanistic scenarios…”
Section: Methodsmentioning
confidence: 96%
“…According to the calculated interaction energies, the intermediate interacting through the O atom (mode A) is more favorable than that interacting through the C atom (mode B). Our present understanding of the mechanism involves attack of silyl enol ether 1 at the iodine atom of XB‐activated ylide 2 to form an enolonium species, with the subsequent rearrangement furnishing 1,4‐dicarbonyl compounds 3 . However, further mechanistic studies are in progress to distinguish between this and other possible mechanistic scenarios…”
Section: Methodsmentioning
confidence: 96%
“…Although the mechanism still remains elusive, the umpolung of ESEs by aryliodanes is generally accepted as a key step in these transformations (Scheme a) . Under the oxidation effect of hypervalent iodine reagents, the conventionally nucleophilic ESEs can react either with themselves or other nucleophilic coupling partners to form the self‐coupling products, or other α‐functionalized carbonyls, respectively, with phenyl iodides as byproducts. In contrast to the well‐established reaction pattern, we present herein a new cross‐coupling reaction between aryliodanes and difluoroenol silyl ethers (DFSEs) in which aryliodanes not only serve as an oxidant but also act as a coupling partner (Scheme b) .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Szpilman and co‐workers demonstrated that aryliodane umpoled ESEs could be trapped by allylsilanes to produce α‐allyl carbonyls . Inspired by their protocol, we assumed that sequentially treating highly electrophilic PhI(OTf) 2 (in situ generated from PhI(OAc) 2 /TMSOTf) with the DFSE 2 a and allyl trimethylsilane could afford the α‐allylic‐α,α‐difluorinated ketone 3 (Scheme c), thus accessing C‐difluoromethylated products by removing the benzoyl group using a Haller–Bauer reaction .…”
Section: Methodsmentioning
confidence: 99%
“…Um diese Beobachtung in einem allgemeineren Kontext zu nutzen, nahmen wir an, dass eine metallfreie α‐Arylierung, welche auf eine Umlagerung des Kohlenstoffgerüst setzt, entwickelt werden kann (Schema c). Unser machanistisches Postulat beinhaltet die Umsetzung eines allgemeinen α‐disubstituierten Keton‐Nukleophils 1 in die Enoloniumverbindung F mit der Hoffnung, dass diese Zwischenstufe selektiv in das Phenonium‐Intermediat G überführt wird – eine nukleophile Ringöffnung würde den Weg zu einer neuartigen Methode für die α‐Arylierungen von Carbonylverbindungen und die Bildung von einem quaternären Zentrum ebnen. Nachstehend berichten wir über die Entwicklung dieser Methode, welche als eine formale metallfreie α‐Arylierung mittels oxidativer C‐C‐Bindungsaktivierung betrachtet werden kann.…”
Section: Methodsunclassified
“…Hierzu zählten: 1) Das Intermediat F könnte ohne Weiteres eliminieren und so zu einer überaus stabilen β‐aryl‐α,β‐ungesättigten Carbonylverbindung 3 führen. 2) Auch wenn es zu keiner Eliminierungsreaktion kommen würde, wäre ein direkter nukleophiler Angriff auf das Intermediat F denkbar, was zur Darstellung des hier unerwünschten α‐funktionalisierten Umpolungsprodukts 2 führen würde . In voller Kenntnis über diese möglichen Herausforderungen begannen wir zunächst, die oxidative C‐C‐Bindungsaktivierung mit dem Ketoester 1 a , einer Verbindung, welche nicht unwesentlich in der vorteilhaften Enol‐Form vorliegt, zu erkunden.…”
Section: Methodsunclassified